Does Financial Development and Corruption reduce the level of Income Inequality? Evidence from Malaysia - Shaharuddin, Norhasimah; Abd. Wahab, Mohd Hafiz; Masdek, Nik Rozila Nik; Abdul Karim, Norzitah; Mohd Zaki, Bushra; Jamaludin, Salwaty (Information Management and Business Review, 2023)
Income inequality is an enduring issue and an important one to address, especially in the new era of digital transformation, as it is a crucial element in promoting persistent income inequality. The theory is that while financial development promotes economic growth, the mixed explanations of previous studies show that this does not always help low-income people in emerging economies. Moreover, the effects of globalization may reinforce motives and increase opportunities for international corrupt practices. It is, therefore, crucial to explore how corruption can be motivated by ineffective rules governing cross-border crimes and how technology can open up new avenues for corrupt behavior, for example by making it easier to find victims, accomplices and money. Profound socio-economic changes can also provide incentives and opportunities for corruption. This study examines how corruption and financial development affect the wealth gap in a developing country like Malaysia over the period 1995 to 2021. The empirical results show that financial development has a positive impact on income inequality. Moreover, the result also shows that corruption control is an insignificant determinant of per capita income in Malaysia. Even though the growth of the financial sector has led to a variety of outcomes, it has only helped to reduce income inequality. Income inequality is negatively and significantly affected by the interaction between financial development and anti-corruption. It is therefore important to promote financial development, prevent corruption and increase government transparency as these factors can promote sustainable economic development and resilience.